2019
DOI: 10.11622/smedj.2019010
|View full text |Cite
|
Sign up to set email alerts
|

Colonic stenting for malignant large bowel obstruction is safe and effective: a single-surgeon experience

Abstract: INTRODUCTION Self-expanding metal stents (SEMS) can be used as a bridge to surgery (BTS) or for palliation in the treatment of malignant large bowel obstruction. This case series evaluates the short-term outcomes of SEMS and success rates over time. METHODS A total of 75 consecutive patients who underwent colonic stenting for malignant colonic obstruction over a period of six years were included. This time period was subdivided into two equal parts for analysis. The procedure was carried out by a single surgeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…A recently published case series describing the experience of a single surgeon from a tertiary institution in Singapore reported that the majority (63.2%) of patients underwent open surgery after insertion of a colonic stent for MBO. [ 32 ] The median time to surgery was 10 (range 0–21) days. In contrast, 84% of patients in our study underwent MIS for resection of the obstructing CRC after colonic stenting as BTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published case series describing the experience of a single surgeon from a tertiary institution in Singapore reported that the majority (63.2%) of patients underwent open surgery after insertion of a colonic stent for MBO. [ 32 ] The median time to surgery was 10 (range 0–21) days. In contrast, 84% of patients in our study underwent MIS for resection of the obstructing CRC after colonic stenting as BTS.…”
Section: Discussionmentioning
confidence: 99%
“…The median interval to definitive curative surgery in our study was 20 (range 6–57) days, which is double that of the finding reported in the study by Tang et al . [ 32 ] It is possible that the longer interval to surgery in our study allowed time for optimisation of the patient before surgery, resulting in a higher proportion of patients receiving MIS. Moreover, the oncological outcomes in patients who had SEMS inserted as BTS were reported in our study, adding to the local data available on colonic stenting for MBO in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies demonstrated the efficacy of this technique and even our recent perspective randomized controlled clinical study demonstrates the effectiveness of this technique but no study, in literature, describes the way of treatment of long neoplastic stenosis using SEMS positioning [9][10][11]. This study demonstrated how is possible to perform endoscopic SEMS positioning to treat neoplastic large bowel obstruction for palliative treatment or as bridge to surgery and describes point by point all passages of this technique.…”
Section: Discussionmentioning
confidence: 99%
“…prevent further bowel ischemia or perforation [4]. The feasibility of primary anastomosis depends on the condition of the colon as well as the patient's hemodynamic status [4].…”
Section: Research Articlementioning
confidence: 99%
“…CRC patients present with acute intestinal obstruction in 8-13% of cases [3]. A total of 75% of obstructing CRCs occur distal to splenic flexure, with the sigmoid colon being the most common location [4]. Malignant colonic obstruction is managed via emergency surgery to relieve the obstruction, to de-function or resect the affected bowel and to…”
Section: Introductionmentioning
confidence: 99%